Decarbonated development of tourist attractions based on system dynamics. (1st January 2013) - Luo, Yuyan; Liao, Zhixue; Ren, Peiyu; Jin, Maozhu; Wang, Jun; Zhang, Ying
Transforming the development way of tourism industry from the extensive mode to intensive one towards low-carbon economy is coming in the context of a variety of global environmental problems. For tourist attractions, how to advocate and achieve decarbonated development based on system engineering is a new subject deserving to be discussed. This paper proposes system dynamics model of scenic area to research the development status of decarbonated tourist attractions system from subsystems of economic operation, social development, environmental protection, constructive guarantee and makes the sensitivity analysis of carbon emissions handling rate in scenic area, and takes Jiuzhaigou Valley as the subject of simulation to do an empirical analysis, finding that carbon emissions handling rate would have a threshold. When reaching the threshold, it will not be the key factor affecting the process of decarbonated development, and carbon emissions per benefit in Jiuzhaigou Valley is declining to meet the requirement of sustainable development and in the process of decarbonated trend.